Pembelajaran Outing Class Melalui Kegiatan Fun cooking dalam Mengembangkan Kreativitas Anak Usia 5-6 Tahun - Fhatri, Zonalisa; Dwi Haryanti; Abdi Susanto; Hari Kiswanto; Wulan Naroh; Wika Wilandari (Institut Agama Islam Negeri Madura, 2024)
This study was conducted to describe the Outing Class learning through fun cooking activities in developing and describing the creativity of 5-6 year old children at the Integrated Islamic Kindergarten Cahaya Toboali and Khoirunnisa Kindergarten in Central Bangka. The type of research used was descriptive qualitative research. This research is included in field research with a qualitative descriptive approach. Observation and interviews were used to collect data, with the data sources referred to as respondents. The data analysis technique used the main components of data reduction, data presentation, and conclusion drawing carried out simultaneously with the data collection process, in a cyclic form during the research process. The results showed that the outing class learning through fun cooking activities at the Integrated Islamic Kindergarten Cahaya Toboali and Khoirunnisa Kindergarten in Central Bangka showed significant benefits for 5-6 year old children. After participating in the Outing Class learning through fun cooking activities, 5-6 year old children at the Integrated Islamic Kindergarten Cahaya Toboali and Khoirunnisa Kindergarten in Central Bangka experienced significant development in their creativity.